2012
DOI: 10.5402/2012/829854
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Changes of Mammalian Nucleoli during Spermatogenesis and Their Possible Role in the Chromatoid Body Assembling

Abstract: Chromatoid body (CB) is a typical cytoplasmic organelle of germ cells, and it seems to be involved in RNA/protein accumulation for later germ-cell differentiation. Despite most of the events in mammals spermatogenesis had been widely described in the past decades and the increase in the studies related to the CB molecular composition and physiology, the origins and functions of this important structure of male germ cells are still unclear. The aims of this study were to describe the nucleolar cycle and also to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 63 publications
0
5
0
1
Order By: Relevance
“…The detection of several mitochondrial elements in CB may confirm the relationship between the nuclear and mitochondrial genomes and that this interaction is passed on from generation to generation (Noce et al, 2001). Research (Peruquetti et al, 2012) has also confirmed a relationship between the mitochondria of spermatocytes and CB and the role of CB in the formation of the midpiece and tail of sperm cells. The relationship between CB and mitochondria may also explain the participation of CB in the synthesis and transport of apocytochrome c, an isoform of cytochrome c whose expression is observed in testicular tissue, and the presence of cytochrome c oxidase (COXI), a significant component of mitochondria (Haraguchi et al, 2005).…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…The detection of several mitochondrial elements in CB may confirm the relationship between the nuclear and mitochondrial genomes and that this interaction is passed on from generation to generation (Noce et al, 2001). Research (Peruquetti et al, 2012) has also confirmed a relationship between the mitochondria of spermatocytes and CB and the role of CB in the formation of the midpiece and tail of sperm cells. The relationship between CB and mitochondria may also explain the participation of CB in the synthesis and transport of apocytochrome c, an isoform of cytochrome c whose expression is observed in testicular tissue, and the presence of cytochrome c oxidase (COXI), a significant component of mitochondria (Haraguchi et al, 2005).…”
Section: Discussionmentioning
confidence: 68%
“…Another hypothesis explains that the nucleoli decrease in size because fragments of them migrate to the cytoplasm of the cells towards the end of prophase I (Peruquetti et al, 2012). The literature suggests that CB assembly occurs at the same time as fragmentation of the nucleolus and that the two processes are correlated (Kotaja and Sassone-Corsi, 2007;Peruquetti et al, 2008Peruquetti et al, , 2010.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…При сперматогенезе происходит клеточная пролиферация с повторными митотическими делениями, дублированием хромосом, мейотическим делением клеток и т.д. для дальнейшего образования гаплоидных сперматид с их последующей дифференциацией в зрелые спермии (18).…”
unclassified